Sepsis (Springer New York, 2018)
The new edition of this volume features a concise yet comprehensive review of sepsis. In addition to thoroughly revised chapters from the previous edition that covers the latest in diagnostics, therapeutics, and antimicrobials, the third edition features new chapters on the economic impact of infections and antibiotics, multi-organ failure in sepsis, and current strategies for training high-performance teams. Written by an international group of experts in the field, Sepsis, Third Edition is a valuable resource that provides the most practical information for clinicians and practitioners who treat this complication in the ICU. .